3D Computational Modeling of Bleb Initiation Dynamics - Strychalski, Wanda (Frontiers in Physics, 2021)
Blebbing occurs in cells under high cortical tension when the membrane locally detaches from the actin cortex, resulting in pressure-driven flow of the cytosol and membrane expansion. Some cells use blebs as leading edge protrusions during cell migration, particularly in 3D environments such as a collagen matrix. Blebs can be initiated through either a localized loss of membrane-cortex adhesion or ablation of the cortex in a region. Bleb morphologies resulting from different initiation mechanisms have not been studied in detail, either experimentally or with theoretical models. Additionally, material properties of the cytoplasm, such as elasticity, have been shown to be important for limiting bleb size. A 3D dynamic computational model of the cell is presented that includes mechanics and the interactions of the cytoplasm, the actin cortex, the cell membrane, and the cytoskeleton. The model is used to quantify bleb expansion dynamics and shapes that result from simulations using different initiation mechanisms. The cytoplasm is modeled as a both viscous fluid and as a poroelastic material. Results from model simulations with a viscous fluid cytoplasm model show much broader blebs that expand faster when they are initiated via cortical ablation than when they are initiated by removing only membrane-cortex adhesion. Simulation results using the poroelastic model of the cytoplasm provide qualitatively similar bleb morphologies regardless of the initiation mechanism. Parameter studies on bleb expansion time, cytoplasmic stiffness, and permeability reveal different scaling properties, namely a smaller power-law exponent, in 3D simulations compared to 2D ones.